Agriculture Play Crucial Role in the Life of Indian Economy. (International Journal of Scientific Research and Management (IJSRM), 2015)
Agricultural sector is the mainstay of the rural Indian economy around which socio- economic privileges and deprivations revolve and any change in its structure is likely to have a corresponding impact on the existing pattern of social equity. Economic development of a country in directly related to the growth of agriculture. Agriculture sector provide the employment opportunity to the peoples. An important aspect of India’s agriculture strategy under the plans has been one of overcoming the institutional constraints to agricultural development. Hitherto it has been chiefly input- led which aims at using various inputs even under the existing structural and institutional framework. Indian agriculture had reached the stage of development and maturity much before the now advanced countries of the world embarked on the path of progress. At that time, there was a proper balance between agriculture and industry and both flourished hand in hand. The share of agriculture in national income is often taken as an indicator of economic development